Pengelolaan Sumberdaya Pesisir Yang Berkelanjutan Bagi Pengembangan Kawasan Pesisir Di Kecamaan Galesong Selatan Kabupaten Takalar - Aulia, Diza; Jufriadi, Jufriadi; Budiharto, Tri (Fakultas Teknik Universitas Bosowa, 2024)
Sustainable Management of Coastal Resources for the Development of Coastal Areas in South Galesong District, Takalar Regency